Antifungal effects of phenolic extract from industrial residues of Aloe vera - Pintos, Beatriz; Martín-Calvarro, Luisa; Piñón, Dolores; Esteban, Alberto; Tello, María L.; Pérez-Urria, Elena; Gómez-Garay, Arancha (Spanish Journal of Agricultural Research, 2018)
This research is concerned with the fungicidal properties of the phenolic extract from industrial residues of Aloe vera used for antifungal treatment of various plant pathogens (Fusarium oxysporum f. sp. radicis-lycopersici, Phaeomoniella chlamydospora, Phaeoacremonium aleophilum, and Sporisorium scitamineum). Six phenolic compounds were identified in this extract from A. vera cortex: aloesin, α-barbaloin, chromone X, isoaloeresin D, β- barbaloin and aloeresin E. Phenolic extract was added to PDA medium at 20 concentrations from 0.32% to 10% and the growth of four different plant pathogenic fungi was tested. Fungal inhibition was calculated in order to evaluate the antifungal efficacy of phenolic extract against pathogens. Inhibition of Sporisorium scitamineum hyphal growth was observed after treatment with the phenolic extract at concentrations higher than 2.5% and a fungistatic effect with a 58.2% mycelia growth inhibition was detected at 3% extract concentration. Inhibition of P. chlamydospora and P. aleophilum hyphal growth was observed at concentrations higher than 4% and 3% respectively. A fungistatic effect with a 71.65% and a 19.87% mycelia growth inhibition was detected at 4.5% and 3.5% extract concentration respectively. About F. oxysporum f. sp. radicis-lycopersici, inhibition of hyphal growth was observed at concentrations higher than 2.5% and a fungistatic effect with a 32.07% mycelia growth inhibition was detected at 3% extract concentration. The results indicate that the tested extract possess antifungal activities against these pathogens at various concentration levels and could be used as a potential natural fungicide in order to control fungi pathogens providing a new use for the A. vera industrial residues.